Censorship and Revolution: The suspected Edition of Nea Politike Dioikesis in Leipzig - Χατζηπαναγιώτη-Sangmeister Ίλια (The Gleaner, 2019)
Based on unknown documents from German archives, this article details a significant case of prohibitive censorship of a modern greek book during the age of Enlightenment. As the unpublished sources show, the secretary of the Prince of Valachia filed in May 1798, some months after the arrest of Rigas Velestinlis, an official accusation against the Greek merchants in Leipzig for having printed a second edition of Nea Politike Dioikesis – the revolutionary manifest of Rigas. The subsequent investigations ordered and conducted by the saxonian authorities prooved that this accusation was unjustified: Neither the Nea Politike Dioikesis nor any other Greek political text were printed in 1798 in Leipzig. The German documents dissolved the bibliographical phantom of a second edition and allow us to examine the combined intervention: the joined forces of ottoman elites and western-european authorities aimed to prevent the publication and circulation of Greek books with contents considered to be subversive.